THE INFLUENCE OF LAL DED'S POETRY ON KASHMIRI CULTURE AND LITERATURE - Zubair Farooq; Dr. Premchandar P (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This research article delves into the profound influence of Lal Ded's poetry on Kashmiri culture and literature. Lal Ded, a renowned 14th-century Kashmiri poet and mystic, holds a significant place in the literary and spiritual traditions of the region. Her verses, known as vatsun, have not only enriched the Kashmiri literary landscape but also left an indelible mark on the cultural ethos of the Kashmiri people. This study aims to explore the multifaceted impact of Lal Ded's poetry by analyzing its role in shaping Kashmiri language, spirituality, social dynamics, and artistic expression. Drawing upon a range of scholarly works, literary analysis, and historical context, this article sheds light on the transformative power of Lal Ded's poetry and its enduring legacy in Kashmiri culture